Loneliness of Supervisors: Its Causes and Their Coping Ways - Kemal Kayıkçı; Gülnar Özyıldırım (Anı Publishing, 2019)
The aim of this study was to determine both the reasons for loneliness of supervisors, which they feel in their individual and organizational activities in their own sub-systems and other sub-systems, and their ways to cope with loneliness. Phenomenology design from qualitative research methods, was used in the research. During the data collection process, twelve supervisors working at management positions (as a chairman or vice chairman) or at supervision office of Antalya Provincial Directorate of National Education were interviewed through semi-structured interview form and the data were analyzed by content analysis method. According to the results of the research, supervisors perceived loneliness as being alone in the social relations and they related the reasons of loneliness in the institution with the nature of the work, institutional and personal values and working conditions. In addition, it can be said that they felt lonely in their other sub-systems relations because of the changes made in the regulation on guidance and supervision, and they experienced this feeling in their social life owing to the effect of their work. Taking up various hobbies and collaborating with friends were among their methods to cope with loneliness. Taking into consideration the effect of loneliness in the workplace, a physical working environment should be prepared for the supervisors in order to increase their communication with their units and other units, and the supervision should be continued with the group.